2017
DOI: 10.4028/www.scientific.net/amm.864.296
|View full text |Cite
|
Sign up to set email alerts
|

EVA Lightweight Concrete Reinforced with Piassava Fiber

Abstract: The residue of Ethylene-Vinyl Acetate (EVA) generated in the footwear industry is an economic and environmental problem as it requires large area for storage in landfills and is not biodegradable or capable of transformation into other polymers. Its use as a lightweight aggregate in mortar and concrete results in a material with lower density but with reduced strength. In this paper, piassava fibers (Attalea funifera Martius) were used as reinforcement of lightweight concrete containing 4% and 6% of EVA, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Untreated piassava fibers were used for the reinforcement of lightweight concrete containing 4% and 6% of ethylene-vinyl acetate to improve the flexural strength of the material [ 95 ]. It was observed that the addition of piassava fiber results in reduced compressive strength, but the presence of fiber has a positive influence on tensile strength.…”
Section: Properties and Importance Of Use In Cementitious Materialsmentioning
confidence: 99%
“…Untreated piassava fibers were used for the reinforcement of lightweight concrete containing 4% and 6% of ethylene-vinyl acetate to improve the flexural strength of the material [ 95 ]. It was observed that the addition of piassava fiber results in reduced compressive strength, but the presence of fiber has a positive influence on tensile strength.…”
Section: Properties and Importance Of Use In Cementitious Materialsmentioning
confidence: 99%
“…In research [11], piassava fibers were used as reinforcement of (LWC) containing 4% and 6% of EVA, with the goal of improving the flexural strength of the material. The experimental results demonstrate that the addition of EVA decreases the density and flexural strength of the concrete in proportion to the amount of addition, but a recovery resistance is got when the piassava fibers are added in amounts of 1 to 2% by volume.…”
Section: Introductionmentioning
confidence: 99%